The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/cen.14723
|View full text |Cite
|
Sign up to set email alerts
|

Clinical management of pregnancy in women with polycystic ovary syndrome: An expert opinion

Abstract: Polycystic ovary syndrome (PCOS) is associated with a higher risk for pregnancy and birth complications according to the specific features associated with PCOS.The features include obesity before and during pregnancy, hyperandrogenism, insulin resistance, infertility, cardiometabolic risk factors, and poor mental health.PCOS is not often recognized as a risk factor for poor pregnancy and birth outcomes in pregnancy care guidelines, while its associated features are. Pregnancy-related risk profile should ideall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 84 publications
0
13
0
Order By: Relevance
“…Moreover, the solubility of alkaloids like piperine in ethanol may contribute to the association with alcohol intake. It is worth noting that a previous study by M. Bahri Khomami et al also reported a positive association between liquor intake and an increased risk of PCOS [39]. Considering these ndings, it is possible that PCOS patients may consume more alcohol, leading to a higher intake of piperine.…”
Section: Discussionmentioning
confidence: 74%
“…Moreover, the solubility of alkaloids like piperine in ethanol may contribute to the association with alcohol intake. It is worth noting that a previous study by M. Bahri Khomami et al also reported a positive association between liquor intake and an increased risk of PCOS [39]. Considering these ndings, it is possible that PCOS patients may consume more alcohol, leading to a higher intake of piperine.…”
Section: Discussionmentioning
confidence: 74%
“…The inclusion criteria were as follows: (1) studies that measured IGFBP-1 and insulin levels in PCOS and non-PCOS women; (2) studies that compared IGFBP-1 and insulin levels among different weight women with or without PCOS; or (3) studies written in English. Diagnostic criteria for PCOS are shown in Table 1.…”
Section: Study Selectionmentioning
confidence: 99%
“…Another study by Sha et al [ 41 ], in a meta-analysis of pregnancy-related outcomes and complications in women with polycystic ovary syndrome undergoing IVF found that women with PCOS had higher risks of miscarriage (OR 1.41); however, the authors concluded by stating that they were unable to perform a further analysis to evaluate the influence of phenotypic variants of PCOS on the prevalence of pregnancy and neonatal complications. Finally, an expert opinion piece published in 2022 on the association between PCOS and miscarriage stated that women with PCOS are at increased risk for ectopic pregnancy, hydatidiform molar pregnancy, and miscarriage, mainly following fertility treatments, but that given that fertility treatments are known risk factors for the outcomes, it is hard to disentangle the association of PCOS per se with these adverse outcomes [ 42 ].…”
Section: Spontaneous Miscarriagementioning
confidence: 99%
“…This controversy about the role of possible confounding factors in the risk between GDM and PCOS unfortunately therefore remains, with a recent expert opinion [ 42 ] concluding that the higher risk of GDM was independent of, yet exacerbated by, obesity in PCOS related to insulin resistance, in contrast to three relatively recent publications including two meta-analyses and a Danish prospective study which all [ 56 , 57 , 58 ] concluded that PCOS may not be an individual risk factor for GDM as pregnancies in PCOS are characterized by factors known to increase the risk of GDM, especially high BMI and fertility treatment.…”
Section: Gestational Diabetes Mellitusmentioning
confidence: 99%